2020
DOI: 10.31234/osf.io/3dz9b
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Partially overlapping neural correlates of metacognitive monitoring and metacognitive control

Abstract: Metacognition describes the process of monitoring one’s own mental states, often for the purpose of cognitive control. Previous research has investigated how metacognitive signals are generated (metacognitive monitoring), for example when people judge their confidence in their decisions and memories. Research has also investigated how these metacognitive signals are used to influence behavior (metacognitive control), for example setting a reminder (i.e. cognitive offloading) for something you are not confident… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…This requires different levels of regulatory control, from fully automated (unaware) to fully conscious (aware), depending on the available level of expertise and routinization (Hacker, 1986). Recent research has shown that cognitive processes related to the monitoring and control of one's own mental states or cognitive processing, are used to influence behavior (Boldt and Gilbert, 2020). Importantly, increasing motor expertise not only automates a well-known action routine, but it also enables better predictions of one's own as well as somebody else's action outcomes (Stapel et al, 2016).…”
Section: Active Self and Sense Of Controlmentioning
confidence: 99%
“…This requires different levels of regulatory control, from fully automated (unaware) to fully conscious (aware), depending on the available level of expertise and routinization (Hacker, 1986). Recent research has shown that cognitive processes related to the monitoring and control of one's own mental states or cognitive processing, are used to influence behavior (Boldt and Gilbert, 2020). Importantly, increasing motor expertise not only automates a well-known action routine, but it also enables better predictions of one's own as well as somebody else's action outcomes (Stapel et al, 2016).…”
Section: Active Self and Sense Of Controlmentioning
confidence: 99%
“…In these experiments, subjects can perform actions such as set reminders, making notes and delegating tasks, 33,34 or report their desire for them. 35 Some research has investigated how metacognitive judgements can influence subsequent cognitive behaviour (i.e., a downward stream from the meta-level to the object level), but only one study so far has explored how this relationship is mapped in the brain. 35 In the other track, researchers investigate EF, also referred to as cognitive control, 30,36 which is closely related to metacognition.…”
Section: Metacognition In Cognitive Neuroscience 21 Operational Defimentioning
confidence: 99%
“…35 Some research has investigated how metacognitive judgements can influence subsequent cognitive behaviour (i.e., a downward stream from the meta-level to the object level), but only one study so far has explored how this relationship is mapped in the brain. 35 In the other track, researchers investigate EF, also referred to as cognitive control, 30,36 which is closely related to metacognition. Note however that EF are often not framed in metacognitive terms in the literature 37 (but see 30 ).…”
Section: Metacognition In Cognitive Neuroscience 21 Operational Defimentioning
confidence: 99%
See 2 more Smart Citations